The epistemological character of isomorphism in the generation of innovation - Rocha, Sued Santos Souza (2018)
This paper presents as its main objective an analysis of the epistemological nature of isomorphism in the generation of innovation in organisations. The present research observed current contents such as analyses of design thinking and isomorphism, with their intra-organisational interactions. It concludes that isomorphism is a frequent practice of managers in organisations who seek to copy structures or actions in order to obtain greater visibility and competitiveness in a specific organisational field. However, innovation is also a prominent way of distinguishing a product for the sake of market competitiveness; as a theoretical contribution it is an excellent form of organisational change, in that it exposes selectively the conceptual proposals of several contributors, focusing on creative modelling for new solutions through design and planning. This study includes diagrams, charts and other elements to meet predictable expectations. They are intended to benefit researchers and other scholars of innovation, in light of the relevance and coverage of this theme.